PENGARUH INFRASTUKTUR EKONOMI DAN SOSIAL DALAM PEMBANGUNAN DAERAH - wahyu dede kusuma (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2019)
This study describes the effect of economic and social infrastructures on regional development in Indonesia. Infrastructures were devided into two parts, they are: economic infrastructures (road, cellular phone, electricity, and clean water access) and social (education) in 33 provinces from 2012 to 2017. This study uses panel data: fixed effect model with cross-section weights (Panel EGLS). From the estimation, we can get the description that all of infrastructures and labor participation give the significant effect to regional development except road. All of those significant infrastructures and labor participation give the positive effect to the regional development. Labor participationgives the biggest impact to regional development followed by electricity and clean water access.